PENERAPAN MODEL PICTURE AND PICTURE UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV MIN 7 PIDIE - Junaidah (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2018)
The purpose of this study was to determine the application of the picture and picture model to increase the learning outcomes of 4th grade students of MIN 7 Pidie. The type of research used is classroom action research (CAR). The subjects of this study were students of 4th grade MIN 7 Pidie, totaling 20 students, consisting of 13 male students and 7 female students. Data collection techniques were carried out using LKS, Student Observation Sheets, Teacher Observation Sheets, Test Questions and Field Notes. The results showed that students progressed in student learning outcomes with the acquisition of the average value of students per each cycle continued to increase, namely: Cycle I the average value was 61.25 with the percentage of completeness in learning 45%, Cycle II the average value 75.25 with a learning completeness percentage of 75% and Cycle III an average value of 81.5 with a 100% learning completeness percentage. In conclusion the application of the picture and picture model increase the learning outcomes of 4th grade students of MIN 7 Pidie